Learning Analysis Using Wordwall Web Based Game Methods to Increase Student Motivation at SMPN Sesean Toraja Utara - Sofyan Sofyan; Anna Pertiwi (Edumaspul: Jurnal Pendidikan, 2024)
The problem in this research is the lack of student motivation to learn at school. This research aims to analyze the word wall web-based game method in increasing student motivation at SMPN 1 Sesean North Toraja. The type of research used in this research is descriptive qualitative research. The subjects in this research were all parties involved in implementing learning using the Wordwall web-based game method to increase student learning motivation at SMPN 1 North Toraja. The object of the research is increasing student motivation at SMPN 1 North Toraja. Data collection techniques are interviews, observation, questionnaires, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of the research include: (1) student questionnaire data regarding the implementation of learning, there were 65% or 14 students who said they did not agree with conventional learning methods, 22% or 5 students said they agreed, while 13% or 3 people who answered were doubtful and 4% or 1 person did not provide an answer. Teacher questionnaire data regarding the use of learning media found that 90% or at least 17 teachers admitted that they had never used IT-based media in the learning process and another 10% of teachers admitted that they had never used IT-based learning media; (2) the problems faced by teachers are not having the resources to use IT-based learning media, lack of facilities and infrastructure and there are still teachers who are comfortable with conventional learning; (3) from the interview results, 90% of students admitted that they were more motivated in learning if they used Wordwall Web-based games in learning and 100% of students admitted that their learning motivation had increased.